ENGAGING OLDER RESIDENTS THROUGH A CIVIC ACADEMY IN AGE-FRIENDLY BOSTON. (11th November 2018) - Bui, C; Coyle, C; Shea, E; Burns, A
Abstract: Age-Friendly Boston identifies the importance of providing civic engagement opportunities for their older residents and aims to be a community "where older residents are involved with making decisions in both public and private sectors and are regularly consulted by elected officials." This presentation will outline the contents of a Civic Academy conducted as part of the Age-Friendly Boston Initiative. The Civic Academy is a cross-sector program geared toward educating older residents in city, state and federal processes, and developing advocacy skills. A mixed-method evaluation was conducted to understand the connection between this educational program and older residents' likelihood to participate in advocacy. Evaluation methods included a pre- and post-test to assess knowledge acquisition as well as follow-up interviews with participants about their activities since course completion. Our evaluation results indicate that the Civic Academy program did have a positive impact on older residents' likelihood to engage in advocacy and was considered a valuable program to participants. We share the process or preparation, practice, and evaluation of the Civic Academy with the goal of replication in other age-friendly communities.